Gender-stratified analyses of symptoms associated with acute coronary syndrome in telephone triage: a cross-sectional study. Issue 6 (25th June 2021) - Wouters, Loes T C M; Zwart, Dorien L M; Erkelens, Daphne C A; De Groot, Esther; van Smeden, Maarten; Hoes, Arno W; Damoiseaux, Roger A M J; Rutten, Frans H
Abstract : Objectives: To identify clinical variables that are associated with the diagnosis acute coronary syndrome (ACS) in women and men with chest discomfort who contact out-of-hours primary care (OHS-PC) by telephone, and to explore whether there are indications whether these variables differ among women and men. Design: Cross-sectional study in which we compared patient and call characteristics of triage call recordings between women with and without ACS, and men with and without ACS. Setting: Nine OHS-PC in the Netherlands. Participants: 993 women and 802 men who called OHS-PC for acute chest discomfort (pain, pressure, tightness or discomfort) between 2014 and 2016. Primary outcome measure: Diagnosis of ACS retrieved from the patient's medical record in general practice, including hospital specialists' discharge letters. Results: Among 1795 patients (mean age 58.8 (SD 19.5) years, 55.3% women), 15.0% of men and 8.6% of women had an ACS. In both sexes, retrosternal chest pain was associated with ACS (women with ACS vs without 62.3% vs 40.3%, p=0.002; men with ACS vs without 52.5% vs 39.7%, p=0.032; gender interaction, p=0.323), as was pressing/heavy/tightening pain (women 78.6% vs 61.5%, p=0.011; men 82.1% vs 57.4%, p=<0.001; gender interaction, p=0.368) and radiation to the arm (women 75.6% vs 45.9%, p<0.001; men 56.0% vs 34.8%, p<0.001; gender interaction, p=0.339). Results indicate that only in women were severe pain (65.4% vs 38.1%, p=0.006; gender interaction p=0.007) and radiation to jaw (50.0% vs 22.9%, p=0.007; gender interaction p=0.015) associated with ACS. Ambulances were dispatched equally in women (72.9%) and men with ACS (70.0%). Conclusion: Our results indicate there were more similarities than differences in symptoms associated with the diagnosis ACS for women and men. Important exceptions were pain severity and radiation of pain in women. Whether these differences have an impact on predicting ACS needs to be further investigated with multivariable analyses. Trial registration number: NTR7331.